Triple-A transnational education (TNE): addressing intercultural challenges - Wang, Jiayi (Frontiers in Communication, 2025)
Transnational education (TNE) creates a dynamic intercultural space where students, staff, managers, and regulators engage with diverse norms, expectations, and institutional practices across borders. The intercultural challenges embedded in TNE remain underexplored in both research and policy. This study introduces the Triple-A TNE Partnership Framework—agility, adaptability, and alignment—as an empirically grounded conceptual model for navigating these complexities. Drawing on a multi-source dataset—123 student surveys, 67 responses from staff, managers, and regulators, 55 parent surveys, 108 regulatory TNE review reports, and 12 in-depth interviews—this study examines how institutions respond to disruption, negotiate structural differences, and manage competing priorities. Agility supports timely, trust-building responses to change. Adaptability enables context-sensitive teaching, assessment, and governance. Alignment fosters coherence among institutional goals, stakeholder roles, and incentive systems. Together, these capabilities offer a practical and theoretically grounded approach to intercultural engagement. The findings also highlight the need for formal institutional support for those delivering TNE. The Triple-A framework provides institutions and regulators with a clear foundation for building successful and sustainable TNE partnerships in an increasingly complex and interconnected global landscape.